Accounting Information System Analysis at PT PLN UID Lampung - Marwah, Siti Anisa; Ali Alam, Iskandar (LPPPIPublishing, 2025)
This study aims to analyze the implementation of Accounting Information Systems (AIS) at PT PLN UID Lampung, including its effectiveness in supporting operational efficiency, data security, process automation, and corporate decision making. In addition, this study also identifies challenges and system development plans to improve the performance and function of the accounting information system. PERMEN BUMN No. PER-18/MBU/10/2014 emphasizes importance technology information For increase Power BUMN competitiveness through accurate data and decision making decision fast. This study uses a qualitative method through direct interviews with key informants, namely Asman AKT AT and PDP at PT PLN UID Lampung. The data obtained were analyzed to understand the implementation, benefits, challenges, and efforts to develop accounting information systems in the company. The results of the study indicate that the implementation of SAP-based accounting information systems has had a significant positive impact on the operational efficiency of PT PLN UID Lampung. This system is able to automate most manual processes, improve data accuracy, and accelerate the completion of financial reports. Special training and technical support are available to assist users in operating the system. However, challenges faced include the adaptation of new users and technical constraints that require third-party vendor intervention.